Analisis Komposisi Mineral Bottom Ash Boiler Pabrik Kelapa Sawit Menggunakan Spektrometer Xrf - Hafiz Rizqa Pratama; Mahyunis . (Rekayasa Material, Manufaktur dan Energi, 2026)
Boiler Bottom Ash is a solid waste generated from the palm oil processing industry that has not been optimally utilized. In fact, this waste contains various inorganic compounds such as silica, calcium oxide, potassium oxide, and phosphorus pentoxide which have potential in agriculture, construction, and industry. Previous studies have shown that boiler Bottom Ash has a high content of oxidized silica, but its chemical composition analysis is still limited. This study aims to analyze the composition of palm oil mill boiler Bottom Ash using X-Ray Fluorescence (XRF) Spectrometer Test. The research method used is a laboratory experimental method with analysis of the mineral composition of boiler Bottom Ash using  X-Ray Fluorescence (EDXRF) Spectrometers. Samples were taken from the combustion of boiler Bottom Ash, then prepared in the form of drying and homogenization before testing. The results showed that boiler Bottom Ash contained 52.43% SiO₂, 19.98% CaO, 9.78% K₂O₅, and 7.88% P₂O₅. These results demonstrate that boiler Bottom Ash has significant potential as an industrial raw material and soil conditioner. This research is expected to support sustainable waste utilization and the circular economy concept.